2008
DOI: 10.1200/jco.2007.14.6738
|View full text |Cite
|
Sign up to set email alerts
|

Unresolved Grief in a National Sample of Bereaved Parents: Impaired Mental and Physical Health 4 to 9 Years Later

Abstract: Parents who have not worked through their grief are at increased risk of long-term mental and physical morbidity, increased health service use, and increased sick leave.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
144
0
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(157 citation statements)
references
References 30 publications
3
144
0
10
Order By: Relevance
“…Those two studies found that 26% of the parents had not worked through their grief, and they were more likely to report symptoms of anxiety and depression than parents who had resolved their grief 4-9 years after the loss [49]. Kreicbergs et al also reported that social support facilitated the grieving process [48].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Those two studies found that 26% of the parents had not worked through their grief, and they were more likely to report symptoms of anxiety and depression than parents who had resolved their grief 4-9 years after the loss [49]. Kreicbergs et al also reported that social support facilitated the grieving process [48].…”
Section: Discussionmentioning
confidence: 96%
“…The present study's primary research question has previously been posed to parents who had lost a child to cancer 4 -9 years earlier [48,49]. Those two studies found that 26% of the parents had not worked through their grief, and they were more likely to report symptoms of anxiety and depression than parents who had resolved their grief 4-9 years after the loss [49].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found that bereaved parents may experience mental health disorders such as depression, anxiety, insomnia, prolonged grief disorder (PGD), post-traumatic stress disorder (PTSD) and suicidal behaviours (Harper, O’Connor, & O’Carroll, 2014; Lannen, Wolfe, Prigerson, Onelov, & Kreicbergs, 2008; Rogers, Floyd, Seltzer, Greenberg, & Hong, 2008). The loss of a child is also associated with worse physical health problems in the long term (Lannen et al, 2008). In China, many families have only one child.…”
Section: Introductionmentioning
confidence: 99%
“…However, Swanson et al's (2007) sample had a higher proportion of mothers with other perinatal losses and also reported no association between this variable and self-reported grief distress one year postmiscarriage. While some mothers may find the presence of living children assists them in managing their grief (Toedter, Lasker, & Alhadeff, 1988), having to support the siblings after the death may contribute to emotional distress in others (Lannen et al, 2008). However, the presence of other children has been found by some researchers to have had no impact on the grief of the women who experienced miscarriage (Swanson et al, 2007).…”
Section: Predictors Of Complicated Griefmentioning
confidence: 91%
“…& Kreicbergs, 2008) and interventions designed for individuals affected by perinatal bereavement need to be tailored to address these challenges (Koopmans et al, 2013).…”
mentioning
confidence: 99%